2022
DOI: 10.1002/ep.14020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diesel and propanol blends on regulated pollutants and polycyclic aromatic hydrocarbons under lean combustion conditions

Abstract: Alcohols such as n-propanol and diesel fuel can be mixed to increase the rate of bioalcohol utilization while reducing harmful pollutants. Examination of exhaust emissions from diesel engines, in terms of both regulated pollutants and unregulated polycyclic aromatic hydrocarbons (PAHs), is very important to the environment, public health, and engine durability. For this purpose, in this study, diesel blends with various n-propanol concentrations (5%, 20%, and 35% by volume) were evaluated in a diesel engine. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…HC emission is significantly lower in the case of lower HRF injection timing (up to 50° bTDC) in almost all LRF premixed shares. At lower HRF injection advancement, opposing cylinder pressure is comparatively higher during HRF injection (than that of maximum injection advancement operation) and air‐fuel mixing time is also comparatively lower which reduces the probability of wall impingement as well as crevice flow, thus resulting in lower HC emission 48,49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HC emission is significantly lower in the case of lower HRF injection timing (up to 50° bTDC) in almost all LRF premixed shares. At lower HRF injection advancement, opposing cylinder pressure is comparatively higher during HRF injection (than that of maximum injection advancement operation) and air‐fuel mixing time is also comparatively lower which reduces the probability of wall impingement as well as crevice flow, thus resulting in lower HC emission 48,49 …”
Section: Resultsmentioning
confidence: 99%
“…At lower HRF injection advancement, opposing cylinder pressure is comparatively higher during HRF injection (than that of F I G U R E 1 0 Variation in maximum cylinder temperature with HRF injection timing and LRF premix ratio.F I G U R E 1 1 Variation of maximum pressure rise rate (MPRR) with HRF injection timing and LRF participation share. maximum injection advancement operation) and air-fuel mixing time is also comparatively lower which reduces the probability of wall impingement as well as crevice flow, thus resulting in lower HC emission 48,49. CO emissions have a similar rationale for combustion quality or its incompleteness.…”
mentioning
confidence: 99%
“…Biodiesel blends containing n-pentanol at concentration of 5%, 20%, and 35% resulted in NO X emission reductions of 13.71%, 26.3%, and 11.86%, respectively, when compared to neat biodiesel. The ignition delay time is increased at higher loads, leading to premixed combustion of which n-pentanol improves, resulting in a reduction of the cooling effect [36,37]. Although the ignition delay time is increased at higher loads, the residence time is reduced at high temperatures, producing less NO X [6].…”
Section: Resultsmentioning
confidence: 99%
“…And it is essential to mitigate the pollution of road dust by reducing pollutants such as PAHs in the various sources of road dust. For example, controlling the emissions of vehicle exhaust, such as exhaust gas from diesel engines, may not only improve engine durability but also reduce the content of pollutants [ 22 ]. Recent studies found that the addition of alcohols to diesel or biodiesel significantly reduced emissions of regulated pollutants and unregulated PAHs from diesel engine exhaust, which provides a positive measure to decrease PAH content in vehicle exhaust [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%